Pelatihan Pembuatan Pestisida Nabati Solusi Pengendalian Hama Thrips Petani Muda Desa Sukowiryo Kecamatan Jelbuk - Halwiyah, Lailatul; Yulianti, Annisa; Maulidina, Niswah Saffanah; Akbar, Muhammad Mizan Ilham; Ramadhan, Adam; Sobah, Naqiyyah Nada; Azzarah; Pradika, Yoga Reno Ayom; Utami, Ratih Apri; Avivi, Sholeh (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Thrips pests are plant pest organisms (OPT) that disturb chili plants in Sukowiryo Village, Jelbuk District which can cause damage to plants, especially on the leaves. Overcoming this problem, PPK ORMAWA HIMASETA held a training on making vegetable pesticides on 22 July 2024 at the AKSATANI secretariat which was attended by 20 young farmers. The training activity aims to improve the ability of young farmers to make and use vegetable pesticides, as well as their impact on plants. The method used the counselling method regarding vegetable pesticides as an alternative effort for control of thrips pests, training in the production of vegetable pesticides, and application on chilli fields. Evaluation was conducted through pre-test and post-test questionnaires to measure knowledge and skills of young farmers. Results of the training showed that the training successful improved the knowledge and skills of young farmers in the production and use of plant-based pesticides.